THE MAIN DIRECTIONS OF MIGRATION PROCESSES AND ECONOMIC CRISES CORRELATION - K. D. Andryushchenko (Publishing House of the State University of Management, 2021)
The article makes an attempt to determine the primacy of the categories “migration process” and “economic crisis”. The paper analyses statistical data of the Federal State Statistic Service of the Russian Federation and the organization for Economic Cooperation and Development on migration processes in Russia. The authors study the possibility of considering the main economic directions of emigration as the reasons of economic crises. The study analyses the number of Russian citizens employed in the countries of the Organization for Economic Cooperation and Development. The article carries out a detailed study of the volume of net capital outflow by the private sector from Russia in 2019-2020. The authors make an attempt to substantiate the thesis about the root cause of migration processes in the system of global transformations. The paper justifies the need for a detailed analysis of macroeconomic indicators of development in order to build a retrospective view of the primacy of the studied processes.